The Application of an Abaqus Preprocessor Based on Python Language in a DAHC Negative Poisson Ratio Structure - Sun, Xiaoting; Yu, Guibo; Zhu, Xiujie; Che, Jinli; Yan, Yuanyuan; Wang, Wei (Crystals (Basel), 2025)
The double-arrow hollow cylinder (DAHC) has excellent mechanical properties under axial compression loads due to its negative Poisson ratio structure. To improve finite element simulation efficiency for parameter optimization analysis, an automatic modeling program for DAHC negative Poisson ratio structures was developed on the ABAQUS platform using Python. The sample was manufactured using selective laser melting additive manufacturing based on the solid model and then simulated using the finite element method. The accuracy of the automatic modeling method was confirmed by comparing load–displacement curves and deformation cloud images with static compression test results. The DAHC automatic modeling program based on Python can reduce workload during parameter optimization analysis and improve finite element analysis efficiency.